Design and development of aircraft systems - Seabridge, A. G. (Aerospace series (Chichester, England), 2013)
Now covering both conventional and unmanned systems, this is a significant update of the definitive book on aircraft system design Design and Development of Aircraft Systems, Second Edition is for people who want to understand how industry develops the customer requirement into a fully integrated, tested, and qualified product that is safe to fly and fit for purpose. This edition has been updated to take into account the growth of unmanned air vehicles, together with updates to all chapters to bring them in line with current design practice and technologies as taught on.